A New Local Turn for Track One Peace Process Research: Anthropological Approaches. Issue 3 (29th July 2021) - Meininghaus, Esther
Abstract : This article argues for a new local turn in peace process research to analyze the perspectives and local embeddedness of peace process participants in Track One negotiations. Historically, peace process research and practice have focused on mediators' strategies for coaxing belligerent disputants into signing agreements. Problems with the implementation of such agreements (i.e., peacebuilding and peacekeeping) are often faulted as the reason for their collapse. However, statistical data points in another direction and raises the following question: To what extent are the set‐up and understanding of peace processes themselves (i.e., peacemaking) implicated in the failure of peace agreements? This article highlights how the different experiences with which peace process participants enter negotiations, and the ways in which they operate at the "local" level in addition to the international diplomatic level, have remained largely unexplored for Track One negotiations. Offering a model that understands peace processes as intersecting, oftentimes informal networks, the article proposes that qualitative—for example, anthropological—research into peace processes can contribute to a critical peace process theory that takes these networks into account. To illustrate this argument empirically, the article draws on the U.N. peace process for Syria.